Where to Draw the Line for Intracranial Hypertension; Opening Pressures and Mortality. Issue 7 (July 2022) - Edwards, Jacob D.; Quinn, Seth A.; Saylors, Seth; McBride, Katherine; Scott, Stephanie; Irish, William; Garcia, Nicole; Toschlog, Eric
Background: Intracranial pressure (ICP) monitoring and treatment is a mainstay of severe TBI management but the relationship between intracranial opening pressure (OP) and outcomes has not been well established. The purpose of our study was to assess the relationship between OP and outcomes in severe TBI patients, with a focus on in-hospital mortality. Methods: Adult blunt TBI patients with ICP monitoring between 2007 and 2017 were evaluated using sequential multivariable binary logistic modeling. Generalized additive model (GAM) was used to evaluate the relationship between OP and death. Odds ratio (OR) and 95% confidence interval (CI) were calculated for measures of strength of association and precision. Results: A total of 182 patients were identified, with 61 (33.5%) having OP >20 mmHG (overall mean ± OP = 19.4 ± 17.8 mmHG). Forty-eight percent, 9% and 8% of patients were discharged to rehabilitation, skilled nursing institution, and home, respectively. Thirty-five percent died in the hospital. A linear relationship was found between OP and log-odds of mortality. OP (OR = 1.07; 95% CI = 1.04-1.11), age (OR = 1.05;95%CI = 1.02-1.07), and injury severity score (ISS) (OR = 1.06; 95% CI = 1.02-1.10) were independently associated with increased odds of death while adjusting for sex, race, and year. Discussion: Elevated opening pressure is strongly predictive of death in severe TBI. Age and ISS are independent predictors of mortality regardless of OP. These results suggest that maintaining low levels of ICP should result in decreased mortality in severe TBI patients. The patient's age and ISS should be considered in the decision-making processes related to ICP utilization and management.